(untitled) (Itinera, 2022)
At the time of Instagramism, social media profiles are characterized by recognizable and homogeneous visual theme. Following the spread of the filter culture which allows greater control over numerous chromo-luministic parameters, users are confronted with a normalization of the notions of editing and color correction before every contents’ online publication. The content creators are capable to creatively make what Lev Manovich defines style of existence, using the post-production tools now maneuverable to achieve the desired representation. In a self-representative but social dispositif, the aesthetics of filter triggers chromatic characterizations and compositions such as the color grid. The paper intends to deepen the theoretical and methodological relationship between the social self-representation and the chromatic practice, with particular attention to the ways in which the coloristic connotations led to pleasant and gratifying presentation of the Self on Instagram platform.